Design and development of fixable clamping for milling machine based on machining performance - Ab Wahab, Norfariza; Abdul Rani, Muhammad Haris; Nordin, Abd Khahar; Nordin, Nor Fauzi; Ibrahim, Mohd Azimin; Basar, Mohd Farriz; Boejang, Hambali (Research India Publications, 2018)
Milling machine vise is one of the common clamping device used in the industry and for learning purposes. The purpose of milling vise is to reduce working time by permitting snappy set-up. It also functions as a supporter during the machining process and help to increase accuracy of the completed parts. However, limited surface of the work-piece can be cut in only one single clamping. This requires the operator to load and unload the clamping vise repeatedly. Obviously, the process is not effective and efficient. In this project, the design of the clamping is presented for flexible positioning of the work-piece during the machining process. This product will allow the manufacturer reduce their setup time and manual inspection. Portable Surface Roughness Tester, SJ-401 is used to evaluate the surface roughness of the work-piece. Delrin and aluminium are used as the work-piece.